Measuring Young Professionals’ Housing Affordability in Greater Kuala Lumpur - Suzylah Sohaimi, Nor; Abdullah, Alias; Shuid, Syafiee (International Journal of Engineering and Technology, 2018)
A plethora of approaches applied for measuring the housing affordability. Undoubtedly, the housing cost and household income are ubiquitous predictors to address the housing affordability. Besides, housing policies also receive an enormous attention in debating this issue. This study, therefore, presents the predictors of transportation cost along with other factors in addressing housing affordability for young professionals. Equally, important, individual life event is also highlighted as this matter is being given less attention. By adopting these dimensions, it is idyllic in associating the study gap. Young professionals are individuals aged between 25 and 35 years old and either working or living in Greater Kuala Lumpur with at least a bachelorâ€™s degree qualification and registered through the professional firm. The purpose of the study is first, to measure young professionalsâ€™ affordability by underpinning the residual income approach and second, to explore the affordability through the housing trajectories concept. Thus, 290 survey data were analysed using the binary logistic regression. The study found that the predictors such as the presence of children, professional for engineer and quantity surveyor, employment status of permanent and other, household expenditure, household income, housing cost, transportation cost, housing location of Petaling Jaya and Putrajaya, are statistically significant to the housing affordability. Â Â